Homo Ludens: The Changing Meaning and Function of Game from Traditional Life to Culture Industry ‘Squid Game’ Example - Ferhat Kaçar (Sakarya İletişim)
Game is a fundamental part of human life and a universal phenomenon. Throughout history, games have played an important role in every age from childhood to adulthood, contributing to personal and social development. However, over time, with the development of industrial processes, games have become a part of the culture industry and this has led to a change in the meaning and function of games. This study emphasises the relationship of the series Squid Game with the game and its changing function. In the theoretical part of the study, the definition of the concept of game and its relationship with culture are evaluated by focusing on Johan Huizinga’s ‘Game Theory’. Then, the traditional children's games in the series Squid Game are analysed in the context of Huizinga's game theory and the function and meaning of the game that has been lost with capitalist life are revealed. In the study, four of the six children's games in the series were analysed using semiotic and discourse analysis methods. These analyses show how the elements of fun, sincerity and enjoyment change under difficult conditions. The findings reveal that economic pressures and social inequalities have transformed the function of games and that children's games have become deadly and cruel in the struggle for survival and the ambition to make money in modern society. As a result, it is understood that children's games in the series have lost their innocence by breaking away from their real ties with the capitalist system.